1972
DOI: 10.1073/pnas.69.12.3805
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium Bromide as a Cooperative Effector of a DNA Structure

Abstract: A salt-induced cooperative conformational transition of a synthetic DNA, poly(dG-dC), is reversed by addition of ethidium bromide. Binding of the dye at high salt concentrations is highly cooperative. Circular dichroism spectra of the complex and the kinetic data support a model for this cooperative binding that is formally equivalent to the "allosteric" one proposed for oligomeric proteins by Monod et al. Thus, double-helical DNA of at least one defined sequence can undergo a cooperative conformational change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(102 citation statements)
references
References 16 publications
12
89
0
1
Order By: Relevance
“…Increased UV absorbance around 295 nm has been found to be related to structural perturbations in the classical B-DNA helix [21]. Lafer et al [22] have earlier shown that double stranded poly(dG-dC) in 4 M NaC1 attain the Z-conformation and an observed absorbance ratio (295/260) of 0.30.…”
Section: Resultsmentioning
confidence: 99%
“…Increased UV absorbance around 295 nm has been found to be related to structural perturbations in the classical B-DNA helix [21]. Lafer et al [22] have earlier shown that double stranded poly(dG-dC) in 4 M NaC1 attain the Z-conformation and an observed absorbance ratio (295/260) of 0.30.…”
Section: Resultsmentioning
confidence: 99%
“…Instead Kappr the apparent association constant was determined from the negative of the limiting slope of the data obtained and napp from the intercept when r/cd = 0. From Eqns (36) and (37) of Gurskii et al [13], it has been shown [14] that for homogeneous DNA polymers…”
Section: Spectrophotometric Binding Studiesmentioning
confidence: 99%
“…Support for an SBS model appears to come from the results of studies of the optical isomerisation of the double stranded synthetic polynucleotide-poly (dG-dC) (Pohl, Jovin, Baehr and Holbrook 1972). Facile interconversion of so called Rand L forms can be achieved by a change in salt concentration alone.…”
Section: Optical Rotationmentioning
confidence: 99%